2021
DOI: 10.1108/jaoc-09-2020-0137
|View full text |Cite
|
Sign up to set email alerts
|

Management Control Systems and Innovation: a levers of control analysis in an innovative company

Abstract: Purpose Building on the growing body of research that has addressed management control systems and innovation, the purpose of this study is to assess the extent and nature of the use of controls in an innovative setting and how they work together unveiling the relationships and tensions amongst the Simons’ levers. Design/methodology/approach This study resorts to an in-depth and single case study in a company that has both a strong orientation to innovation and stable control practices in place. Evidence was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…We contribute to the literature by examining the relationship between MCS and the operational activities during the strategic change process in an innovation [3] setting. We know that many MCS are commonly used in innovation settings to accomplish organizational goals (Akroyd and Maguire, 2011; Akroyd et al , 2016; Barros and Ferreira, 2019, 2021; Davila, 2000; Feeney and Pierce, 2018; Frare et al , 2021; Henri and Wouters, 2020; Müller-Stewens et al , 2020; Pan Fagerlin and Lövstål, 2020). The management accounting literature has also shown that MCS can facilitate the implementation of strategy (Kober et al , 2007; Otley, 2016), which are necessary to support changes to innovation activities (Bisbe and Malagueño, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We contribute to the literature by examining the relationship between MCS and the operational activities during the strategic change process in an innovation [3] setting. We know that many MCS are commonly used in innovation settings to accomplish organizational goals (Akroyd and Maguire, 2011; Akroyd et al , 2016; Barros and Ferreira, 2019, 2021; Davila, 2000; Feeney and Pierce, 2018; Frare et al , 2021; Henri and Wouters, 2020; Müller-Stewens et al , 2020; Pan Fagerlin and Lövstål, 2020). The management accounting literature has also shown that MCS can facilitate the implementation of strategy (Kober et al , 2007; Otley, 2016), which are necessary to support changes to innovation activities (Bisbe and Malagueño, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…managers must perform “purposeful interventions” to create dynamic tension. However, some companies struggle to do this (Barros and Ferreira, 2022; Bedford, 2015; Curtis and Sweeney, 2017). While we know that managers are central to this task, the extant research provides little insight into why some managers successfully create dynamic tension (Biswas and Akroyd, 2022; Lövstål and Jontoft, 2017; van der Kolk et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, diagnostic controls are a management-by-exception mode of control, where the managers focus on deviations from established goals and standards and only occasionally intervene when exceptions arise that need to be addressed (Bisbe et al, 2007;Simons, 1995). However, some managers fail to engage in this balancing act (Barros and Ferreira, 2022;van der Kolk et al, 2020). Behavioural complexity is a core element of a manager's ability to support the organisation in various ways depending on the task.…”
Section: Behavioural Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Innovation can be considered the raison d’être of start-ups, and a growing body of research has shown that management control systems (MCSs) can foster innovation (Akroyd and Maguire, 2011; Barros and Ferreira, 2021; Henri and Wouters, 2020; Lill et al , 2021) and contribute to the success of start-ups (Davila et al , 2010; Gomez-Conde et al , 2021). However, the existing MCS literature has largely neglected the multifaceted nature of innovation.…”
Section: Introductionmentioning
confidence: 99%